2004
DOI: 10.1007/s11123-004-7573-1
|View full text |Cite
|
Sign up to set email alerts
|

Scale Economies and Efficiency in U.S. Agriculture: Are Traditional Farms History?

Abstract: The structural transformation of agriculture in recent decades has raised serious concerns about the future of the family farm. This study examines the economic performance of U.S. farms, to explore the potential of smaller farms to compete with larger entities, and ultimately to survive in this rapidly changing environment. We use deterministic and stochastic frontier methods and survey data to measure and evaluate factors underlying scale economies (SEC) and efficiency (SEF) of corn-belt farms for 1996-2001.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
66
0
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 18 publications
10
66
0
8
Order By: Relevance
“…The ranking of efficiency scores by farm size does not change when the bias corrected efficiency scores are used (i.e., 70%, 63%, 54%, and 42%, respectively). These results are consistent with the findings of Weersink, Turvey, and Godah (1990) and Paul et al (2004) that technical efficiency is positively related to farm size. There was not much variation in technical efficiency scores by farm specialization although crop farms are slightly more efficient (61%) than diversified farms (59%) and livestock farms (59%).…”
Section: Technical Efficiency Estimates By Farm Size and Specializationsupporting
confidence: 92%
See 1 more Smart Citation
“…The ranking of efficiency scores by farm size does not change when the bias corrected efficiency scores are used (i.e., 70%, 63%, 54%, and 42%, respectively). These results are consistent with the findings of Weersink, Turvey, and Godah (1990) and Paul et al (2004) that technical efficiency is positively related to farm size. There was not much variation in technical efficiency scores by farm specialization although crop farms are slightly more efficient (61%) than diversified farms (59%) and livestock farms (59%).…”
Section: Technical Efficiency Estimates By Farm Size and Specializationsupporting
confidence: 92%
“…10 These results are contrary to the results by Paul et al (2004) who found small family farms to be less efficient in terms of both their scale of operation and technical aspects of production than large farms. The mean difference in scale efficiency by farm specialization was not statistically significant: crop farms (93%), diversified farms (94%), and livestock farms (92%).…”
Section: Scale Efficiencymentioning
confidence: 90%
“…In fact, for some scholars a small family farm is more efficient than other kind of farms in which the property is in the hands of many people such as cooperatives or corporate farms (Schmitt 1991;Gorton and Davidova 2004); on the contrary, according to other studies, traditional small family farms are not efficient (Paul et al 2004). The reason of a good level of efficiency in small farms is due to a low level of transaction cost (Hagedorn 1994).…”
Section: Aim Of the Research And The Theoretical Framework Of The Studymentioning
confidence: 99%
“…As will be shown later, the study sought to contemplate this aspect through the estimation of a stochastic frontier model where the output variable includes wages earned in off-farm activities. The justification for considering the income earned in off-farm activities is based primarily on the following points (Paul et al, 2004;Chavas et al, 2005;Olson;Vu, 2007): i) such activities would use common inputs to rural production, and ii) affect the economic performance of producers. In this context, as stated by Guanziroli et al (2001) about the Brazilian family farming scenario, the possibility to generate income outside the family production unit is a factor that can determine the capacity of accumulation and thus the viability of any production system.…”
Section: Contextmentioning
confidence: 99%
“…The total value of production includes that corresponding to livestock, crops and value-added from agribusiness. The addition of the wages earned in off-farm activities to the total value of production aims to deal with the point mentioned above, whereby the income from off-farms activities should be considered as a product under the justification that such activities use inputs common to rural production and affect the economic performance of family farmers (Paul et al, 2004). One should indicate, though, that this procedure implies the imposition of the hypothesis that both categories of activities (inside or outside the establishment) are considered as equally important by producers (Solís, 2005).…”
Section: Stochastic Production Frontiermentioning
confidence: 99%